Analyzing the Effects of Supply Chain Management and Skilled Workforce Competency on Project Schedule Delays and Their Implications for Occupational Accident Prevention: Evidence From PT Daidan Group - Timoer Indraprasta Hermet; Ayudhia Pangestu; Marihot Simanjuntak (Dinasti International Journal of Digital Business Management, 2026)
Project schedule delays and the high risk of workplace accidents remain major issues in construction project management, particularly those related to ineffective supply management and insufficient expert workforce skills. This study aims to analyze the effect of supply management and expert workforce skills on workplace accident prevention, with schedule delays as a mediating variable at PT Daidan Group. The research design employs a quantitative descriptive approach using a survey method. The population consists of technical workers and experts, with a sample of 157 respondents selected using purposive sampling based on the Slovin formula. Data were collected through structured questionnaires using a Likert scale. The data analysis technique applied is Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that supply management and expert workforce skills have a positive and significant effect on schedule delays and workplace accident prevention. Schedule delays are also found to have a significant effect on workplace accident prevention and act as a mediating variable between independent and dependent variables. Inventory management and job knowledge dimensions are identified as dominant factors in improving operational effectiveness and workplace safety. These findings suggest that effective supply chain management and enhanced workforce competencies can significantly reduce delays and improve safety performance. The discussion highlights the importance of integrating supply management, human resource development, and project time control in creating a safe and efficient work environment. Therefore, companies are recommended to strengthen inventory control systems, enhance workforce training programs, and optimize project time management to support operational performance and sustainable safety culture